Longitudinal research on mental health and behavioural problems of children and youth: New findings - Sanson, A; Smart, D (My University, 2011)
Longitudinal studies have long been recognised as important vehicles for obtaining high-quality evidence about the determinants of development across the lifespan, as well as casting light on developmental processes in general (Farrington, 1991; Rutter, 1994). Among their advantages are their ability to track continuities, discontinuities, ‘critical periods’, and transition points in development; test models of causal relationships between early events or characteristics and later outcomes; identify developmental sequences and pathways; tease out the relative and interacting contributions of diverse factors that impact on development; and through these, provide evidence on optimal times and foci for interventions to interrupt maladaptive pathways and promote positive development.
Keywords: Child Development; Health -- Mental; Health and wellbeing; Childhood and child development; Health; Child Development; Mental; Childhood and child development; Health and wellbeing